An open-label, dose-escalation study to evaluate the safety and pharmacokinetics of CEP-9722 (a PARP-1 and PARP-2 inhibitor) in combination with gemcitabine and cisplatin in patients with advanced solid tumors. Issue 4 (April 2016) - Awada, Ahmad; Campone, Mario; Varga, Andrea; Aftimos, Philippe; Frenel, Jean-Sébastien; Bahleda, Rastilav; Gombos, Andrea; Bourbouloux, Emmanuelle; Soria, Jean-Charles
Abstract : Poly (ADP-ribose) polymerase-1 (PARP-1) inhibitors may potentiate chemotherapy by hindering DNA damage repair pathways. CEP-9722 is the prodrug of CEP-8983, a selective inhibitor of PARP-1 and PARP-2. Preclinical studies and a prior phase 1 study suggested that CEP-9722 may cause less myelosuppression than has been observed with other oral PARP inhibitors. The primary objective of this study was to determine the maximum-tolerated dose of CEP-9722 in combination with gemcitabine and cisplatin in patients with advanced solid tumors. All patients received cisplatin 75 mg/m 2 on day 1 and gemcitabine 1250 mg/m 2 on days 1 and 8 of a 21-day cycle. Patients who completed one cycle of chemotherapy alone continued chemotherapy in combination with CEP-9722 150, 200, 300, or 400 mg orally twice daily on days 2–7, with dose-limiting toxicity assessed in cycle 2. Patients experiencing clinical benefit could continue treatment until disease progression or unacceptable toxicity. Thirty-two patients enrolled; 18 patients completed cycle 1 and received chemotherapy plus CEP-9722. The median (range) treatment administration with CEP-9722 was five (1–12) cycles. No patient experienced dose-limiting toxicity with CEP-9722 treatment. Grade 3/4 hematologic adverse events included neutropenia (28%) and leukopenia (11%); adverse events led to discontinuation in 33% of patients. One patient achieved complete response, three had partial responses, and 11 had stable disease; however, the relative contribution of CEP-9722 and/or the chemotherapeutic agents cannot be determined from this single-arm design. This study was discontinued before determination of the maximum-tolerated dose because of highly variable CEP-8983 exposure in all cohorts and toxicity, particularly chemotherapy-induced myelosuppression.